Eventual nomeação de Bispo Auxiliar de raça Chinesa para a diocese de Macau (1967)
This archival document comprises a 1967 Portuguese colonial administrative file (Process No. 1–7–1, File D-7-1) originating from the Ministry of the Overseas Territories and the Ministry of Foreign Affairs, concerning ecclesiastical governance in the Province of Macau under Portuguese administration. It includes a confidential memorandum dated 3 June 1967 from the Governor of Macau to the Ministry, reporting internal divisions among the diocesan clergy, criticism of Bishop Paulo Tavares’s authoritarian pastoral administration, and concerns regarding the influence of his brother, who served as his Secretary. The file documents diplomatic exchanges between Lisbon and the Holy See—particularly with Archbishop Agostino Casaroli (erroneously referred to in the original as ‘Monsignor Samoré’)—regarding the Holy See’s preliminary consideration of appointing a Chinese-origin Auxiliary Bishop for Macau as a contingency measure in anticipation of potential sovereignty changes. It records the appointment of Chinese and Eurasian clergy to key posts—including Canon António André Ngan (Vicar General and Chantre), Reverend João Paulo de Sousa (Rector), and Reverend Cláudio Maria Leão Ló (Vice-Rector)—and notes the candidacy of Reverend Dr. Massa. The document further details Vatican assessments of Bishop Tavares’s suitability for reassignment to Rome or a Central American nunciature, and reflects sustained Portuguese diplomatic efforts to forestall the appointment of a Chinese auxiliary bishop. Dated between March and June 1967, the file is held in the Arquivo Histórico Ultramarino (AHU), Conselho Ultramarino—Índia, Caixa 14.
Keywords: Bishop Paulo Tavares; Bishops of Macau; Diocesan Clergy Divisions; Ecclesiastical Governance in Macau; Foreign Affairs Archives (Portugal); Governor of Macau Memorandum; Holy See Diplomatic Relations; Macau Portuguese Colonial Administration; Ministry of Foreign Affairs Portugal; Ministry of the Overseas Territories; Transcription